Perfil del migrante y refugiado venezolano en Perú 2018-2022 - Lizarzaburu Bolaños, Edmundo (2025)
Venezuelan migration in Peru has faced the Peruvian State with many legal, operational and humanitarian challenges. The National Institute of Statistics and Informatics prepared the Survey “Living conditions of the Venezuelan population residing in Peru” which describes the characteristics of this population. Based on this data, this research has been developed with the purpose of developing a profile of the Venezuelan migrant and refugee in Peru. The average profile of this citizen has these characteristics: she is a woman, a young adult, his marital status is cohabiting, his partner is another Venezuelan, he has a diversified secondary education and suffers from asthma.